2017
DOI: 10.5812/ijcm.7233
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine Among Iranian Cancer Patients in South of Iran

Abstract: Background: Use of complementary and alternative medicine (CAM) among cancer patients is not exactly defined. Objectives: The aim of this study was to determine the use of CAM and associated factors among Iranian cancer patients, reasons behind this use, satisfaction and information about complementary and alternative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Systematic reviews promote a present basis for any observation and might broaden new study ideas. At the beginning of a written document, it allows readers to enjoy and become expertise in the contemporary tendencies of troubles and clears up the importance of revolutionary studies [ 10 ]. Tappen (2016) demonstrated that literature reviews involve methodically determining, finding, and examining materials that are associated with the study question [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews promote a present basis for any observation and might broaden new study ideas. At the beginning of a written document, it allows readers to enjoy and become expertise in the contemporary tendencies of troubles and clears up the importance of revolutionary studies [ 10 ]. Tappen (2016) demonstrated that literature reviews involve methodically determining, finding, and examining materials that are associated with the study question [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reliability of quantitative research is correlated with its consistency, stability, agreement, reproducibility, repeatability, and homogeneity. Nevertheless, validity refers to how well-founded and accurate an instrument or a study measure is [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the studies conducted by Kang et al [24], Demir et al [25] and Amirmoezi et al [26], a prayer is the most frequently used CAM method with respect to body and mind practices, regardless of the religion practised (89,6% -92,2%).…”
Section: Mementioning
confidence: 99%
“…According to the studies conducted by Stanisz et al [16] and Wode et al [28], the complementary and alternative medicine is more often used by younger patients, below the age 45, while Bauml et al [29], Garland et al [31] and Ali-Shtayeh et al [33] report that the age of 65 or below determined a higher frequency of using CAM [26,28,30].Sárváry et al [22] report that residents of towns or cities use complementary medicine more often than the residents of villages(89,8% and 76.5% respectively).…”
Section: Mementioning
confidence: 99%
“…The results of the conducted studies show that Iranians have a positive attitude towards complementary medicine and the demand for such therapies is increasing (12). However some of them have methodological limitations like using questionnaires, which are not validated as well as the limited number of participants that prevent generalizing the results (13).…”
Section: Introductionmentioning
confidence: 99%